Problems of ESG-Reorganization of Russian Metallurgical Corporations - Yu. M. Tsygalov (Управленческое консультирование)
The development of environmental programs in modern conditions is characterized by the ESG transformation of the economy. In the EU, which is the most important importer of Russian steel products, a new carbon tax will be levied from 2025–2026, which will increase the costs of domestic producers by more than 20%. The peculiarity of the new tax is that it applies to the industry value chain, including suppliers and consumers of metal, which jeopardizes other sectors of the national economy.The purpose of the study is to identify the problems and risks generated by the transition of Russian ferrous metallurgy companies to ESG principles of management. The object of research is ESG transformation of the economy. The subject of the study is the problems and risks of the Russian ferrous metallurgy formed by the ESG transformation. General scientific methods were used, such as: analysis, synthesis, abstraction, modeling, generalization. It is established that the ESG transformation of the economy makes the restructuring of Russian metallurgical companies inevitable. At the same time, domestic companies lag behind Western ones in the development of technologies that lead to a zero carbon footprint. Inefficient work to reduce the carbon footprint leads to the payment of carbon tax on foreign markets, fines on the domestic market, prevents the receipt of “green” financing. Starting from 2026, the financial condition of metallurgical companies will rapidly deteriorate. The implementation of the Targeted (intensive) development scenario provided for by the “Strategy of Socio-economic Development of the Russian Federation with low Greenhouse Gas Emissions until 2050” and the active support of the state will help to maintain the position in the markets.